Pengaruh Video Tiktok Terhadap Pengetahuan dan Sikap Ibu Hamil Tentang Gizi Selama Kehamilan - Sari, Lia Artika; Herinawati, Herinawati; Susilawati, Enny; Sari, Dita Mayang (NHM PRESS, 2022)
Malnutrition in pregnant women can cause risks and complications, including anemia and bleeding, while in fetus can cause birth defects and low birth weight. TikTok videos are a medium social media with the most users. Short videos that are less than 3 minutes long able to attract the attention of the millennial generation to absorb various information health. This research is a quasi-experimental research which aims to determine the effect of TikTok Videos on knowledge and attitudes of pregnant women about nutrition at Simpang Parit Health Center in 2021. The population in this study was 132 pregnant women and 76 . samples were taken using purposive sampling method respondents. The data obtained were tested univariately and bivariately using the test Paired Simple Test statistics. The results of the analysis of the level of knowledge and attitudes of pregnant women before and after given health education through TikTok Video obtained p-value (0.000) < (0.05) which means that there is a significant difference after being given education health using TikTok Videos. TikTok videos are influential in increasing mother's knowledge and attitudes pregnant about nutrition during pregnancy. It is hoped that further researchers can develop this research further on nutrition needed during pregnancy with other things that can be studied and discussed in research